Diffuse Neurofibroma in a Patient with Unknown History of NF1 - Mahmoud A. K. Ebrahim; Mishal M. AlMutairi; Khaled M. Hindi; Jassem M. Bastaki (Case Reports in Otolaryngology)
Malignant peripheral nerve sheath tumor (MPNST) is a rare disease in the parotid gland with a poor prognosis in most cases. The disease most often develops in the setting of neurofibromatosis type 1 (NF1) but can also occur sporadically. Herein, we report a rare case of MPNST in the parotid gland, in a patient with no previous history of NF1. Initial investigations of the patient, which consisted of laboratory investigations, ultrasound imaging of the swelling, fine-needle aspiration (FNA), computed tomography (CT) scan, and magnetic resonance imaging (MRI) of the neck and swelling, were compatible with a benign pleomorphic adenoma of the parotid gland. However, intraoperatively, the dissection was challenging as the tumor was adherent to the neighboring tissue. A diagnosis of MPNST arising from a diffuse neurofibroma was established based on clinicopathologic features of the disease. The patient, who exhibited clinical features compatible with (NF1), proceeded for radiotherapy following surgery to continue his treatment.